Protection Duration of COVID-19 Vaccines: Waning Effectiveness and Future Perspective - Zhuang, Chunlan; Liu, Xiaohui; Chen, Qi; Sun, Yuxin; Su, Yingying; Huang, Shoujie; Wu, Ting; Xia, Ningshao (Frontiers in Microbiology, 2022)
The coronavirus disease 2019 (COVID-19) vaccines have very successfully decreased the disease risk as we know; some key information remains unknown due to the short development history and the lack of long-term follow-up studies in vaccinated populations. One of the unanswered issues is the protection duration conferred after COVID-19 vaccination, which appears to play a pivotal role in the future impact of pathogens and is critical to inform the public health response and policy decisions. Here, we review current information on the long-term effectiveness of different COVID-19 vaccines, persistence of immunogenicity, and gaps in knowledge. Meanwhile, we also discuss the influencing factors and future study prospects on this topic.